Method for realizing MXene surface modification by using solid irradiation
Through the combination of solid irradiation method and organic salt, the in-situ modification of MXene material is achieved, which solves the problem of oxidation and degradation of MXene material in oxygen/water environment, retains the intrinsic characteristics of the material and improves the antioxidant ability.
Patent Information
- Application Number
- CN202510043631.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
MXene materials are prone to oxidation and degradation reactions in oxygen/water environments, resulting in the material losing its original structure and characteristics. The existing modification methods are complex and cannot effectively avoid oxidation and degradation.
In-situ modification of MXene material is achieved by solid irradiation method and organic salts, and functional modification of MXene surface is achieved through ionic liquid intercalation and electron beam irradiation to avoid oxidation and degradation in solvent media.
It effectively avoids the oxidative degradation of MXene materials, retains the intrinsic characteristics of the material, improves the anti-oxidation degradation ability, simplifies the modification process, and improves the grafting efficiency and modifier utilization rate.
Smart Images

Figure CN119875203A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of modification and preparation of functional nanofillers, and relates to a method for realizing surface modification of MXene by solid irradiation, and specifically to a preparation method for realizing surface functional modification of MXene in one step by solid irradiation grafting modification technology. Background Art
[0002] Two-dimensional transition metal carbides, nitrides or carbonitrides, namely MXene materials, are a new type of two-dimensional nanomaterials obtained by etching away the A element from the layered material MAX phase. The chemical formula of MXene can be expressed as M n+1 X n T x , where M represents an early transition metal element (Sc, Ti, V, Cr, Zr, Nb, Mo, etc.), X represents C and / or N elements, T x Represents the surface end group (—O, —OH, —F, etc.). Due to the diversity of MAX phase composition and structure, MXene materials derived from it have also become the largest family of two-dimensional materials, with more than 100 theoretically predicted and more than 40 synthesized so far.
[0003] Thanks to its layered structure and unique properties, MXene materials have shown great application potential in the fields of electrode materials, membrane separation materials, microwave shielding and absorption materials, sensor materials, nanogenerators, etc. However, in the actual research and application process, there are still many problems and difficulties in the preparation and application of MXene materials. In particular, affected by the surface functional groups, MXene materials are prone to oxidative degradation reactions in oxygen / water environments to generate TiO2, causing the material to lose its original properties. Therefore, in the chemical modification process of MXene materials, the solution system needs to be degassed. Although it can partially slow down the oxidation reaction, it will make the reaction conditions and reaction steps complicated, and it is still impossible to avoid the oxidative degradation of the MXene material itself [Chemistry of Materials, 2017. 29(11): 4848-4856]. How to avoid Ti3C2T x The oxidative degradation of nanosheets while retaining the intrinsic properties of the material has always been the core issue and difficulty in the preparation and functional modification of MXene materials.
[0004] In view of this, if an effective method for modifying MXene materials can be developed to reduce the oxidative degradation of the material itself, it will be of great significance to the application of MXene materials in the field of functional materials. Summary of the invention
[0005] The first object of the present invention is to solve the above-mentioned shortcomings and provide a simple and efficient method for modifying MXene materials.
[0006] The method of the present invention for realizing in-situ modification of MXene materials by means of solid irradiation method and organic salt comprises the following steps: Step (1), mixing and stirring the layered material MAX phase, an etchant and deionized water to obtain a solution blend product; Furthermore, the mass ratio of the layered material MAX phase to the etchant is 100:1.0-50, and the mass ratio of deionized water to the etchant is 100:10-10.
[0007] Furthermore, the stirring time is 12 to 24 hours; and the stirring temperature during the magnetic stirring process is usually set below 100° C. to avoid large amounts of deionized water from volatilizing.
[0008] Further, the layered material MAX phase is one of Ti3SiC2, Ti2AlC, Ti3AlCN, V2AlC, Ti3AlC2, Ti3ZnC2, Ti2ZnC, Ti2ZnN and V2ZnC; Further, the etchant is one of hydrogen fluoride, HCl / LiF mixed solution, NaHF2, KHF2, and NH4HF2; Step (2), centrifuging the above solution blend product to obtain an etching product, then adding the etching product to an ionic liquid (IL) solution, stirring at room temperature for 12-48 hours for intercalation, and obtaining an ionic liquid intercalation product after centrifugation; The ionic liquid is an ionic liquid containing unsaturated double bonds; preferably, the ionic liquid containing unsaturated double bonds is an imidazole ionic liquid; wherein the cation structural formula is as follows: Wherein R1 is a C2-C23 alkyl or a C2-C24 alkenyl; R2 is a C2-C24 alkenyl; the anion in the ionic liquid is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - or (CF3SO3)2N - ; The mass percentage concentration of the ionic liquid is 0.01-50%; the solvent of the ionic liquid is one of deionized water, methanol, ethanol, N,N-dimethylformamide and chloroform.
[0009] Step (3), placing the ionic liquid intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation to obtain an irradiated product; The irradiation is electron beam irradiation, and the experimental conditions are room temperature, air or nitrogen environment; The radiation absorbed dose is 1 to 500 kGy.
[0010] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain a modified MXene material.
[0011] The solvent is one of deionized water, methanol, ethanol and chloroform.
[0012] The second object of the present invention is to provide a MXene material with surface modification achieved by solid irradiation, which is prepared by the above method.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) During the chemical modification of MXene materials, the materials are very susceptible to oxidation degradation reactions in an oxygen / water environment, generating TiO2, causing the materials to lose their original structure and properties. The present invention does not require degassing treatment, and obtains an organic salt-modified MXene intercalation solid material through ion intercalation, which is then centrifuged to obtain an intercalation solid powder, and irradiates the dry powder in a step to achieve functional modification of the MXene surface, thereby avoiding oxidation and degradation of the MXene material in a solvent medium, eliminating the interference of the solvent medium, and being able to well guarantee the structure and properties of the material itself, providing convenience for the subsequent preparation and application of MXene composite materials.
[0014] (2) In the traditional preparation method, the surface modification of MXene materials has problems such as low grafting efficiency, which greatly limits the application of MXene materials. The present invention uses the reactivity of double-bonded ionic liquids between MXene layers (surfaces) to achieve in-situ chemical bond grafting under the action of electron beams, showing high grafting efficiency and modifier utilization rate. The modifier utilization rate and grafting rate are close to 100%, with good atom economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 These are SEM images of the materials before and after etchant treatment, where A is the SEM image of Ti3AlC2 (MAX phase material), B is the SEM image of the product after etching and intercalation treatment (MXene material), and C is the SEM image of the product after irradiation grafting modification.
[0016] Figure 2 FTIR curves before and after irradiation and solvent extraction treatment, wherein curve a is the infrared spectrum of the intercalation product after extraction in comparative example 1, and curve b is the infrared spectrum of the final product of example 1.
[0017] Figure 3 : are XRD result diagrams of samples before and after ionic liquid intercalation, curve a is the XRD curve of the product before ionic liquid intercalation in Example 1, and curve b is the XRD curve of the product after ionic liquid intercalation.
[0018] Figure 4 : XPS spectra of ionic liquid intercalation before and after electron beam irradiation, wherein curve a is the Ti2p curve of the intercalation product in Example 1 before irradiation, and curve b is the Ti2p curve of the intercalation product after irradiation.
[0019] Figure 5 The thermal gravimetric graphs of MXene before and after irradiation modification, wherein curve a is the thermal gravimetric curve of the non-intercalated product etched in Example 1, curve b is the thermal gravimetric curve of the intercalated product, and curve c is the thermal gravimetric curve of the product after irradiation treatment and solvent extraction. DETAILED DESCRIPTION
[0020] As mentioned above, in view of the shortcomings of the prior art, the inventors of this case proposed the technical solution of the present invention after long-term research and extensive practice, which is mainly based on at least the following: (1) The present invention adopts a three-step method, firstly adding the layered material MAX phase, the etchant and the deionized water into a tetrafluoroethylene round-bottom bottle, stirring with a magnetic pole, obtaining an etching product, and then obtaining an ionic liquid intercalation product (solid powder) through ionic liquid intercalation treatment, and using electron beam irradiation to achieve the grafting modification between the double-bonded ionic liquid and the surface group of the MXene material. On the one hand, the grafting reaction of the double-bonded ionic liquid is completed in a non-solvent system (solid powder state), which can effectively avoid the oxidation and degradation of the MXene material in the solvent medium, and well retain the original structure of the material. On the other hand, the presence of the surface grafted ionic liquid can effectively improve the antioxidant degradation ability of the MXene material, which facilitates the subsequent preparation and application of the MXene composite material. (2) The present invention uses the double-bonded ionic liquid to simultaneously achieve the intercalation treatment and surface chemical grafting modification of the MXene material, which effectively simplifies the experimental operation steps and facilitates the preparation of the MXene composite material. (3) The preparation method of the present invention only requires the use of commonly used solution blending and centrifugal processing equipment, and the industrial preparation is simple. The equipment required for the radiation is a commonly used radiation source.
[0021] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0022] The present invention provides a MXene material modification method, comprising the following steps: Step (1), mixing and stirring the layered material MAX phase, an etchant and deionized water to obtain a solution blend product; Step (2), centrifuging the solution blend product to obtain an etching product, then adding it to an ionic liquid solution and stirring it at room temperature, and centrifuging it to obtain an ionic liquid intercalation product; wherein the ionic liquid is an ionic liquid containing an unsaturated double bond; Step (3), placing the ionic liquid intercalation product in a polyethylene ziplock bag for radiation irradiation to obtain an irradiated product; Step (4), dissolving the irradiated product and centrifuging it to obtain a modified MXene material.
[0023] The layered material MAX phase is one of Ti3SiC2, Ti2AlC, Ti3AlCN, V2AlC, Ti3AlC2, Ti3ZnC2, Ti2ZnC, Ti2ZnN and V2ZnC; The etchant is one of hydrogen fluoride, HCl / LiF mixed solution, NaHF2, KHF2, and NH4HF2; The ionic liquid (IL) is an ionic liquid containing an unsaturated double bond; preferably, the ionic liquid containing an unsaturated double bond is an imidazole ionic liquid; wherein the cation structure is as follows: Wherein R1 is a C2-C23 alkyl or a C2-C24 alkenyl; R2 is a C2-C24 alkenyl; the anion in the ionic liquid is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - or (CF3SO3)2N - ; Its mass percentage concentration is 0.01 wt% to 50 wt%, which can be selected according to the actual intercalation modification needs, for example, 1wt%, 2wt%, 3wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, but not limited to this.
[0024] The solvent is one of deionized water, methanol, ethanol, N,N-dimethylformamide and chloroform.
[0025] The production process of the above-mentioned MXene material with excellent antioxidant properties in the present invention is as follows: First, the layered material MAX phase, etchant and deionized water are added to a tetrafluoroethylene round-bottom bottle and stirred with a magnetic stirrer for 12 hours. The mass ratio of the layered material MAX phase to the etchant is 100:1.0-50, and the mass ratio of deionized water to the etchant is 100:10-10. The stirring temperature during the magnetic stirring process is usually set below 100°C to avoid a large amount of deionized water volatilization.
[0026] Secondly, the solution blend product is centrifuged to obtain an etching product, which is then added to an ionic liquid solution and stirred at room temperature for 12 hours. After centrifugation, an ionic liquid intercalation product is obtained in the form of a solid powder; Next, the ionic liquid intercalation product obtained above is placed in a polyethylene ziplock bag for radiation irradiation to obtain a radiation-modified product. The irradiation is electron beam irradiation. The experimental conditions are room temperature, air or nitrogen environment, and the irradiation absorbed dose is 1 to 500 kGy, and finally an irradiation-modified product is obtained.
[0027] The technical solution of the present invention is further explained below in conjunction with several preferred embodiments, but the experimental conditions and setting parameters therein should not be regarded as limiting the basic technical solution of the present invention. And the protection scope of the present invention is not limited to the following embodiments.
[0028] In this embodiment and its comparative example, Ti3AlC2 is used as the MAX phase material, and the MAX phase material is from Jilin Yiyi Technology Co., Ltd., and hydrogen fluoride solution etchant is used as an example. The ionic liquid is 1-vinyl-3-methylimidazolium chloride.
[0029] Example 1 Step (1): First, add 1.0 g Ti3AlC2, 0.5 g NH4HF2 and 5 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0030] Step (2), adding the above-mentioned etching product into a 1.0 wt% aqueous solution of 1-vinyl-3-methylimidazolium chloride, stirring at room temperature for 12 hours, and centrifuging to obtain an intercalation modified product.
[0031] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 10 kGy at room temperature.
[0032] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0033] Example 2 Step (1): First, add 1.0 g Ti3AlC2, 1.0 g NH4HF2 and 5 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0034] Step (2), adding the above-mentioned etching product into a 1.0 wt% aqueous solution of 1-vinyl-3-methylimidazolium chloride, stirring at room temperature for 12 hours, and centrifuging to obtain an intercalation modified product.
[0035] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 20 kGy at room temperature.
[0036] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0037] Example 3 Step (1): First, add 1.0 g Ti3AlC2, 0.8 g NH4HF2 and 8 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0038] Step (2), adding the above-mentioned etching product into a 2.0 wt% aqueous solution of 1-vinyl-3-methylimidazolium chloride, stirring at room temperature for 12 hours, and centrifuging to obtain an intercalation modified product.
[0039] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 50 kGy at room temperature.
[0040] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0041] Example 4 Step (1): First, add 1.0 g Ti3AlC2, 1.2 g NH4HF2 and 10 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0042] Step (2), adding the above-mentioned etching product into a 3.0 wt% aqueous solution of 1-vinyl-3-methylimidazolium chloride, stirring at room temperature for 12 hours, and centrifuging to obtain an intercalation modified product.
[0043] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 80 kGy at room temperature.
[0044] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0045] Example 5 Step (1): First, add 1.0 g Ti3AlC2, 1.2 g NH4HF2 and 10 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 24 hours, and then centrifuge to obtain an etching product.
[0046] Step (2), adding the above-mentioned etching product into a 20.0 wt% aqueous solution of 1-vinyl-3-decyl imidazole bromide, stirring at room temperature for 24 hours, and centrifuging to obtain an intercalation modified product.
[0047] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 150 kGy at room temperature.
[0048] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0049] Example 5 Step (1): First, add 1.0 g Ti3AlC2 and 20 ml hydrofluoric acid solution into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 24 hours, and then centrifuge to obtain an etching product.
[0050] Step (2), adding the above-mentioned etching product into a 50.0 wt% aqueous solution of 1-vinyl-3-octylimidazole chloride, stirring at room temperature for 18 hours, and centrifuging to obtain an intercalation modified product.
[0051] Step (3), placing the intercalation product obtained above in a polyethylene ziplock bag for radiation irradiation, the radiation absorption dose is 100 kGy, and the irradiation is performed at room temperature.
[0052] Step (4), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0053] Comparative Example 1 Step (1): First, add 1.0 g Ti3AlC2, 0.5 g NH4HF2 and 5 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0054] Step (2), adding the above-mentioned etching product into a 1.0 wt% aqueous solution of 1-vinyl-3-methylimidazolium chloride, stirring at room temperature for 12 hours, and centrifuging to obtain an intercalation modified product.
[0055] Comparative Example 2 Step (1): First, add 1.0 g Ti3AlC2, 0.5 g NH4HF2 and 5 g deionized water into a tetrafluoroethylene round-bottom bottle, stir with a magnetic stirrer at room temperature for 12 hours, and then centrifuge to obtain an etching product.
[0056] Step (2), placing the above-obtained etched product in a polyethylene ziplock bag for radiation irradiation, with an absorbed radiation dose of 10 kGy at room temperature.
[0057] Step (3), dissolving the irradiated product in a solvent and subjecting it to centrifugal treatment to obtain an ionic liquid-modified MXene material.
[0058] The chemical composition of the samples obtained in Example 1, Comparative Example 1 and Comparative Example 2 was tested, and the microstructure of the MXene material was characterized and analyzed.
[0059] like Figure 1 As shown, Figure 1 A in the figure is the SEM image of the material before etching. Figure 1 B is the SEM image of the product (MXene material) after etching and intercalation treatment. Figure 1 C in Figure 1 is the SEM image of the product after irradiation grafting modification. Figure 1 It can be seen that after etching, the material has a flake structure, and the material structure has not changed significantly before and after irradiation modification. The material changes from block to flake, indicating that the material is successfully etched and the corresponding MXene material is obtained.
[0060] In order to further confirm the existence of ionic liquids in MXene materials, Figure 2 The composition of the material was characterized and analyzed by infrared spectrometer. Among them, curve a is the infrared spectrum of the intercalation product after extraction in comparative example 1, and curve b is the infrared spectrum of the final product of example 1. The results show that compared with curve a, curve b has obvious characteristic absorption peaks of ionic liquids, indicating that a certain amount of ionic liquids are present in the product. At the same time, since the sample has been fully extracted with methanol before characterization, the free ungrafted ionic liquid is removed. This also indirectly shows that the ionic liquid with double bonds has been successfully grafted onto the MXene material.
[0061] Figure 3 The intercalation behavior of the ionic liquid was characterized and analyzed, where curve a is the XRD curve of the product before ionic liquid intercalation in Example 1, and curve b is the XRD curve of the product after ionic liquid intercalation. The results show that after intercalation modification, the interlayer spacing of the MXene material increases significantly, which indicates that the ionic liquid is indeed intercalated into the interlayer of the material, which also provides a basis for realizing the radiation grafting modification of MXene materials using ionic liquids.
[0062] Figure 4The XPS spectra of ionic liquid intercalation before and after electron beam irradiation, where curve a is the Ti2p curve of the intercalation product before irradiation in Example 1, and curve b is the Ti2p curve of the intercalation product after irradiation. The results show that the characteristic curve of the Ti element did not change significantly before and after irradiation, and the presence of tetravalent Ti was not observed, which indicates that the solid irradiation modification technology will not affect the structure of the MXene material itself, providing a guarantee for the subsequent use of MXene materials.
[0063] Figure 5 The following is the thermogravimetric graph of MXene before and after irradiation modification, where curve a is the thermogravimetric curve of the unintercalated product etched in Example 1, curve b is the thermogravimetric curve of the intercalated product, and curve c is the thermogravimetric curve of the product after irradiation treatment and solvent extraction. The results show that in curve b, the intercalated product has obvious degradation weight loss of the intercalation agent (ionic liquid) around 300°C, while in curve c, after the product is irradiated and modified and solvent extracted, the thermogravimetric curve does not change significantly and the weight loss percentage almost coincides with curve b, which indicates that the ionic liquid on the surface (interlayer) of MXene is almost in situ grafted to the material surface under the action of the electron beam, showing high grafting efficiency and modifier utilization.
[0064] The above embodiments are not limitations of the present invention, and the present invention is not limited to the above embodiments. As long as the requirements of the present invention are met, they belong to the protection scope of the present invention.
Claims
1. A method for surface modification of MXene using solid irradiation, characterized in that: The method comprises the following steps: Step (1), mixing and stirring the layered material MAX phase, an etchant and deionized water to obtain a solution blend product; Step (2), adding the solution blended product to the ionic liquid solution after centrifugation, stirring at room temperature for intercalation, and obtaining an ionic liquid intercalation product after centrifugation; wherein the ionic liquid is an ionic liquid containing an unsaturated double bond, and its mass percentage concentration is 0.01 to 50%; Step (3), placing the ionic liquid intercalation product in a polyethylene ziplock bag for radiation irradiation to obtain an irradiated product; Step (4), dissolving the irradiated product and centrifuging it to obtain a modified MXene material.
2. The method according to claim 1, characterized in that In step (1), the mass ratio of the layered material MAX phase to the etchant is 100:1.0-50.
3. The method according to claim 2, characterized in that In step (1), the mass ratio of deionized water to etchant is 100:10-10.
4. The method according to claim 1 or 2, characterized in that: The layered material MAX phase in step (1) is one of Ti3SiC2, Ti2AlC, Ti3AlCN, V2AlC, Ti3AlC2, Ti3ZnC2, Ti2ZnC, Ti2ZnN or V2ZnC.
5. The method according to claim 1 or 3, characterized in that: The etchant in step (1) is one of hydrogen fluoride, HCl / LiF mixed solution, NaHF2, KHF2, and NH4HF2.
6. The method according to claim 1, characterized in that In step (1), the stirring time is 12 to 14 h, and the stirring temperature is lower than 100 °C.
7. The method according to claim 1, characterized in that The ionic liquid containing unsaturated double bonds in step (2) is an imidazole ionic liquid, and its cationic structure is as follows: Wherein R1 is a C2-C23 alkyl or a C2-C24 alkenyl; R2 is a C2-C24 alkenyl; the anion in the ionic liquid is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - or (CF3SO3)2N - .
8. The method according to claim 1, characterized in that The radiation irradiation in step (3) is electron beam irradiation; the radiation irradiation conditions are room temperature, air or nitrogen environment.
9. The method according to claim 1, characterized in that: The absorbed dose of radiation exposure in step (3) is 1 to 500 kGy.
10. A MXene material with surface modification achieved by solid irradiation, obtained by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of two-dimensional layered MXene material
CN107098344A
MXene-based nano composite wave-absorbing material and preparation method thereof
CN111629575A
Method for immobilizing MXene by covalent bonding of ionic liquid and product thereof
CN111785534A
Polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyion liquid and preparation method thereof
CN119161612A
Electrochemical systems comprising mxenes and max phase compositions and methods of using the same
US20180309125A1